Fracture risk in people with developmental disabilities: results of a large claims data analysis. Issue 1 (January 2017) - Büchele, G.; Becker, C.; Cameron, I.; Auer, R.; Rothenbacher, D.; König, H.; Rapp, K.
Abstract Summary Age- and sex-specific fracture rates of 18, 000 people with developmental disabilities aged 0–69 years were compared to the general population. Age-standardized incidence of femoral fracture was 4.8- and 7.1-fold higher in women and men, respectively. Comparable fracture risks to the general population occurred 10–15 years earlier in females and 20–40 years earlier in males. Introduction Previous studies suggested that fracture risks in people with developmental disabilities (DD) may be higher than in people in the general population. However, there are no current sufficiently large studies to compare age- and sex-specific fracture rates of single fracture types. Methods People with DD and incident fractures were identified by routine data of a health insurance company. Fractures in the general population were derived from the official fracture statistics. Age-specific and age-standardized fracture incidences were analyzed. To compare fracture risks in people with DD with that of the general population incidence ratios were calculated. Results Between 2008 and 2010, 148 femoral fractures and 469 other fractures were observed in nearly 18, 000 people with DD aged 0–69 years. The three most frequent fracture types leading to hospital admission were fractures of the femur, lower leg/ankle, and shoulder/arm. For femoral fractures, a particularly high risk was observed in children and adolescents with DD. In adults with DD, the risk of femoral fractures increased with increasing age. Even if the youngest age category was not considered, the age-standardized incidence was 4.8- and 7.1-fold higher in women and men, respectively. For all other fracture types, except fractures of forearm/hand and of pelvis, people with DD had also higher fracture incidences than the general population. Conclusions People with DD have a high fracture burden. Comparable risks of femoral fracture, for example, occurred about 10–15 years earlier in females and even 20–40 years earlier in males with DD than in the general population.